Move for Change Part II: a European survey evaluating the impact of the EPDA Charter for people with Parkinson's disease. Issue 3 (3rd October 2012) - Stocchi, F.; Bloem, B. R.
Abstract : Background and purpose: The Move for Change campaign is a three‐part series of pan‐European surveys designed by the European Parkinson's Disease Association (EPDA) to assess the impact that the EPDA Charter for People with Parkinson's disease (PD) has had since its launch in 1997. Here, we report results from the second survey, focusing on the third right of the Charter; that is, 'all patients have the right to have access to support services'. Although the level of evidence for different support services varies, it is important to ensure that patients can access services with clinically proven benefits. Methods: This survey comprised nine questions administered online via the EPDA and PD organization Web sites. Accessibility of support services was defined as ' services/medication/multidisciplinary healthcare professionals, etc. being available and on hand to patients when required '. Results: Neurologists and general practitioners (GPs) received highest accessibility results (90.0 and 87.0% of respondents, respectively), with moderate results for physiotherapists (68.0%) and PD organizations (72.0%) and lower results for PD specialist nurses (26.0%), occupational therapists (23.0%), and counselors (27.0%). Support provided by neurologists and PD specialists was considered to be 'very helpful' by 59.0 and 55.7%, respectively, whilst only 31.8% of respondents gave such favorable ratings to GPs. Funding of services was variable across Europe. Conclusions: These data demonstrate the challenges faced by PD patients in accessing the adequate care and support required throughout the course of their disease. These findings can assist healthcare professionals and policymakers in improving access to support services for patients and their families across Europe.